Circular RNAs as a potential source of neoepitopes in cancer - Xia, Jiaqi; Li, Shuai; Ren, Baorui; Zhang, Pengxia (Frontiers in Oncology, 2023)
Neoepitopes have attracted much attention as targets for immunotherapy against cancer. Therefore, effective neoepitope screening technology is a crucial step in the development of personalized vaccines. Circular RNAs (circRNAs) have single-stranded continuous circular structure and are generated through back-splicing. Various circRNAs remain poorly characterized so far, although emerging evidence suggests that a few translated circRNAs play a role in cancer. In the present study, circRNA was used as a source of neoepitope, which is a novel strategy as circRNA-derived neoepitopes have never been explored previously. The present study reports CIRC_neo (circRNA-derived neoepitope prediction pipeline), which is a comprehensive and automated bioinformatic pipeline for the prediction of circRNA-derived neoepitopes from RNA sequencing data. The computational prediction from sequencing data requires complex computational workflows to identify circRNAs, derive the resulting peptides, infer the types of human leukocyte antigens (HLA I and HLA II) in patients, and predict the neoepitopes binding to these antigens. The present study proposes a novel source of neoepitopes. The study focused on cancer-specific circRNAs, which have greatly expanded the source pool for neoepitope discovery. The statistical analysis of different features of circRNA-derived neoepitopes revealed that circRNAs could produce long proteins or truncated proteins. The generated peptides were completely new to the human body and could, therefore, exhibit high immunogenicity. Importantly, the circRNA-derived neoepitopes that could bind to HLA were identified. The circRNAs were systematically analyzed in the present study, which revealed potential targets and novel research clues for cancer diagnosis, treatment, and prospective personalized vaccine research.